USE OF GRAPHIC PROCESSORS FOR CONSTRUCTION OF THE GEOLOGICAL MEDIA SEISMIC IMAGES - Vyzhva, S.; Lisny, G.; Kruhlyk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The new algorithm and appropriate software for construction of two dimensional and three dimensional seismic images of inhomogeneous anisotropic images were developed. Graphic processing units were used for this problem solution. The main input data type for this software is common shot point seismograms with free configuration. The possibility of velocity models and seismic images construction using free vertical coordinate of sources and receivers was provided. For determination of velocity model of geological media the multidimensional velocity spectra of seismic waves are used. The method of anisotropic decomposition of seismic image is used as well. The comparison of seismic images obtained using graphic processors and individual software as well as cluster calculation system and leading companies software for pre-stack migration was done. The real field common shot point seismograms were used as input data. These seismograms were obtained for area with complex geological structures. The seismic data were characterized by incorrect space sampling of common shot point seismograms. The stability of developed calculation scheme against incorrect space sampling was demonstrated on the basis of obtained results. Additionally, more precise velocity model detection was shown on the basis of accounting of wave propagation anisotropy. The efficiency of graphic processor use for straight transformation of common shot point seismograms into seismic images was shown as well.